2011
DOI: 10.1161/circulationaha.110.976969
|View full text |Cite
|
Sign up to set email alerts
|

Blocking of Frizzled Signaling With a Homologous Peptide Fragment of Wnt3a/Wnt5a Reduces Infarct Expansion and Prevents the Development of Heart Failure After Myocardial Infarction

Abstract: Background-The molecular pathways that control the wound healing after myocardial infarction (MI) are not completely elucidated. One of these pathways is the Wnt/Frizzled pathway. In this study, we evaluated Frizzled as a novel therapeutic target for MI. These Frizzled proteins act as receptors for Wnt proteins and were previously shown to be expressed in the healing infarct. Methods and Results-Wnt/Frizzled signaling has been studied for decades, but synthetic ligands that interfere with the interaction betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
121
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(126 citation statements)
references
References 34 publications
1
121
3
1
Order By: Relevance
“…4 In the present study, we found that the presence of myofibroblasts, as indicated by immunohistochemistry (in which we excluded blood vessels) as well as mRNA expression (that may in part reflect α-SMA from blood vessels) for α-SMA, was higher in the infarcted tissue as compared with remote tissue and correlated not only with IM BL but also with the estimated change in IM over time in the Control-MI group, suggesting that, indeed, myofibroblasts contribute to infarct contraction. In contrast to our previous study in mice, in which UM206 treatment increased myofibroblast presence in the infarcted area, 11 myofibroblast presence was lower in the infarcted myocardium of UM206-treated swine as compared with Control-MI, particularly in swine with a large MI, despite the observation that the reduction in IM was larger. It should be noted, however, that infarct size as a percentage of the left ventricle in mice is much larger than the infarct size in swine in the present study, and therefore mechanical stress within the murine infarcts is expected to be larger.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…4 In the present study, we found that the presence of myofibroblasts, as indicated by immunohistochemistry (in which we excluded blood vessels) as well as mRNA expression (that may in part reflect α-SMA from blood vessels) for α-SMA, was higher in the infarcted tissue as compared with remote tissue and correlated not only with IM BL but also with the estimated change in IM over time in the Control-MI group, suggesting that, indeed, myofibroblasts contribute to infarct contraction. In contrast to our previous study in mice, in which UM206 treatment increased myofibroblast presence in the infarcted area, 11 myofibroblast presence was lower in the infarcted myocardium of UM206-treated swine as compared with Control-MI, particularly in swine with a large MI, despite the observation that the reduction in IM was larger. It should be noted, however, that infarct size as a percentage of the left ventricle in mice is much larger than the infarct size in swine in the present study, and therefore mechanical stress within the murine infarcts is expected to be larger.…”
Section: Discussioncontrasting
confidence: 99%
“…Administration of UM206 promotes migration of fibroblasts to the infarcted area by inhibition of Wnt/Fzd signaling, and thereby modulates the scar formation in the infarcted area. 11 In accordance with our recent study in mice, 11 we found in the present study that treatment with UM206 for 5 weeks reduced infarct mass as compared with its baseline measurement. This reduction in infarct mass was accompanied by a decreased LV dilation, as measured in awake animals with echocardiography, between 3 and 5 weeks after MI in swine treated with UM206.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…21) In other reports, blocking of Wnt/β-catenin signaling was shown to avert adverse remodeling or improve cardiac function in animal models of myocardial infarction. [22][23][24][25] In spite of such a context-dependency, Wnt/β-catenin signaling is thought to play a pivotal role in the progression of cardiac dysfunction/heart failure. 26) In the canonical Wnt/β-catenin pathway, DKK1 (Dickkopf1) basically inhibits the formation of a ternary complex consisting of LRP5/6, Frizzled, and the Wnt ligand followed by inhibition of the canonical Wnt/β-catenin pathway.…”
Section: Wnt/β-catenin Signaling In the Heartmentioning
confidence: 99%
“…Как было по казано недавно Laeremans и др. [42], пептид UM206 блокирует рецепторы, приводя к уменьшению размеров инфаркта и улучшению функционального восстановления сердца. Эти результаты доказывают, что UM206 обладает эффектом, близким к эффекту Sfrps в показате лях восстановления сердца, что далее подтвер ждает логическое обоснование того, что блоки рование рецептора (как показано в нашем ис следовании, повышением белков Sfrp) являет ся эффективным для Wnt3a и его нежелатель ного влияния на миокард.…”
Section: обсуждение результатовunclassified